Do outro lado da câmera: o homem simbólico no processo fotográfico de Luiz Franceschi - Santos, Giselle Godoy Verdi França dos (2022)
Since antiquity, whererever human beings have passed, they have left traces and records of their existence in the form of images. Over the time, the way these records are made have evolved along the dominant technology at each period. However, the human will to make them has remained the same. Within this perspective, the purpose of this research is to reflect on why human beings have always had the will to register the world through images, having as context the beginning of the 20th century and the work of the photographer Luiz Franceschi, in a perspective in which the photographer represents the subject who, for some reason, yearns to register the world around him, being photography the symbolic product that resulted from this process. According to Kossoy, all photography has its origin from the desire of an individual who, at some point and for some reason, at some place or time, was motivated to register a given aspect of reality. To resolve these issues, this research articulates an analysis based on the theorists Morin, Cassirer, Debray and Mitcham. Morin brings the theoretical basis to enunciate the birth of a new consciousness in Homo sapiens. The desire to continue in the world gave rise to this new subjective consciousness that opens access to thinking about fictitious things, allowing the production of symbolic products, through which it perpetuates its existence and denies the oblivion caused by the passage of time. Cassirer, on the other hand, brings the theoretical basis for thinking about issues regarding the human being and the symbolic system, through which they access and interpret the world around them, where art, religion, and science, for example, are part. Based on Debray’s assumptions, the role of the image, its evolution and its effects in different societies, from Antiquity to the present era, is analyzed, where it is understood that the image is what survives from the past and is the that bridges the gap between the absent and the present, which allows the perpetuation of memory and the return of what was through the (re)remembrance that the image and/or photography provides, giving mortal beings a possibility to continue in the world through them. Finally, the analyzes of these three theorists come together to think about the manifestation of technology in the photographer’s exercise from the four manifestations of technology brought by Carl Mitcham, which are the technology as an object, as knowledge, as activity and as volition.